2014
DOI: 10.1177/0145482x1410800403
|View full text |Cite
|
Sign up to set email alerts
|

Straight from the Source: Perceptions of Students with Visual Impairments about Graphic Use

Abstract: Introduction This study analyzed the responses of a survey of students with visual impairments in Canada and the United States about their use of tactile and print graphics. Demographic, Likert scale, and open-ended questions focused on perceptions of quality, preferences, instruction, and strategies. Methods Percentages of agreement for tactile and print graphic users are reported. Comparisons were made between the two groups. Results Students felt positive about the quality of the graphics, but density and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 13 publications
3
31
0
3
Order By: Relevance
“…The interpreting ability is an essential requirement for expertise in problem-solving (Larkin & Reif, 1979). Researchers showed that graphs could be utilized to help physics and mathematics learning (Supalo et al, 2016;Zebehazy & Wilton, 2014). The ability to interpret, recognize, and work with graphs involves mathematical skill and processes (Friel et al, 2001).…”
Section: Interpreting Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interpreting ability is an essential requirement for expertise in problem-solving (Larkin & Reif, 1979). Researchers showed that graphs could be utilized to help physics and mathematics learning (Supalo et al, 2016;Zebehazy & Wilton, 2014). The ability to interpret, recognize, and work with graphs involves mathematical skill and processes (Friel et al, 2001).…”
Section: Interpreting Graphsmentioning
confidence: 99%
“…Graphs could be utilized to help physics and mathematics learning (Supalo, Humphrey, Mallouk, Wohlers, & Carlsen, 2016;Zebehazy & Wilton, 2014). The ability to interpret, recognize, understand, and work with graphs involves mathematical skills and processes (Friel, Curcio, & Bright, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning environment the student experiences is one of the few factors that can be influenced and optimised, and therefore is the most important factor in developing mathematical skills. Research has shown that tactile materials and audible graphs could be used to aid the teaching of mathematics and physics to visually impaired students (Supalo, Humphrey, Mallouk, David Wohlers, & Carlsen, 2016;Zebehazy & Wilton, 2014).…”
Section: How Visually Impaired Students Learnmentioning
confidence: 99%
“…In engineering, science, technology, and mathematics, information is often expressed in graphical representations (Zebehazy & Wilton, 2014), graphs and pictures. For visually impaired high school students this manner of receiving information is a challenge, since they both experience the world differently than people with full vision, as well as being unable to receive printed information.…”
Section: Introductionmentioning
confidence: 99%